Real-Time Intraoperative Surgical Guidance System in the da Vinci Surgical Robot Based on Transrectal Ultrasound/Photoacoustic Imaging With Photoacoustic Markers: An Ex Vivo Demonstration - Song, Hyunwoo; Moradi, Hamid; Jiang, Baichuan; Xu, Keshuai; Wu, Yixuan; Taylor, Russell H.; Deguet, Anton; Kang, Jin U.; Salcudean, Septimiu E.; Boctor, Emad M. (IEEE robotics and automation letters, 2023)
This letter introduces the first integrated real-time intraoperative surgical guidance system, in which an endoscope camera of da Vinci surgical robot and a transrectal ultrasound (TRUS) transducer are co-registered using photoacoustic markers that are detected in both fluorescence (FL) and photoacoustic (PA) imaging. The co-registered system enables the TRUS transducer to track the laser spot illuminated by a pulsed-laser-diode attached to the surgical instrument, providing both FL and PA images of the surgical region-of-interest (ROI). As a result, the generated photoacoustic marker is visualized and localized in the da Vinci endoscopic FL images, and the corresponding tracking can be conducted by rotating the TRUS transducer to display the PA image of the marker. A quantitative evaluation revealed that the average registration and tracking errors were 0.84 mm and 1.16°, respectively. This study shows that the co-registered photoacoustic marker tracking can be effectively deployed intraoperatively using TRUS+PA imaging providing functional guidance of the surgical ROI.